Oxidized low-density lipoprotein induces M2-type differentiation of macrophages to promote the protracted progression of atherosclerotic inflammation in high-fat diet-fed ApoE -/- mice: Oxidized LDL promotes atherosclerosis in mice - Zhang, Bo; Xia, Weichang; Zhou, Jingqun; Lv, Jianfeng; Dai, Qiuting; Li, Xiangyan; Tian, Qinqin; Liu, Xijian; Du, Xuan; Tu, Rong; Liu, Shouyi (Cellular and Molecular Biology, 2023)
In this study, the significance of oxidized low-density lipoprotein (ox-LDL) in promoting the progression of atherosclerosis was investigated by inducing the differentiation of macrophages into the M2 subtype within a high-fat diet-induced ApoE -/- mouse model. The study also evaluated the effects of β2-AR agonists and blockers on this process. Ox-LDL was found to have significantly promoted the differentiation of macrophages into the M2 type and induced related functional alterations. Furthermore, it activated the pyroptosis pathway and encouraged the release of lactate dehydrogenase. The administration of β2-AR agonists intensified these processes, while β2-AR blockers had the opposite effect. In animal experiments, the model group displayed elevated numbers of M2-type macrophages beneath the aortic root intima, an increased rate of plaque destruction, and the formation of atherosclerotic plaques compared to the control group. The SAL (Salbutamol) group exhibited even more severe plaque development than the model group. Conversely, the ICI (ICI118551) group demonstrated M2-type macrophage levels comparable to the control group, with a higher plaque destruction rate than controls but significantly lower than the model group, and no atherosclerotic plaques. These findings suggest that ox-LDL promoted the differentiation of recruited monocytes into M2-type macrophages, leading to a shift in the inflammatory response from M1 to M2 macrophages. This alteration resulted in the persistence of atherosclerotic inflammation, as M2-type macrophages were prone to cell membrane rupture (such as pyroptosis), contributing to the continuous recruitment of circulating monocytes and heightened inflammatory reactions within atherosclerotic plaques. Consequently, this process fueled the progression of atherosclerosis.